A comparative study on quality of life among youths with an without disabilities - Jani, Rohana; Alias, Abd Aziz; Bandar, Nur Fatihah Abdullah; Arunasalam, Ruth Selvaranee (Universiti Putra Malaysia, 2018)
The objective of this paper is to compare the self-perceived Quality of Life (QoL) between disabled and non-disabled youths in Malaysia using the WHOQOL-BREF (World Health Organisation Quality of Life - Abbreviated version) instrument. A cross-sectional questionnaire-based survey of 300 disabled students and a control group comprising 523 non-disabled students from Malaysian higher learning institutions were the subjects for this study. The score for each domain was computed using the formula outlined by WHOQOL-BREF. Descriptive analysis was used to analyse the characteristics of the respondents. Due to the non-normality of the score distribution, nonparametric Mann-Whitney and Kruskal-Wallis tests were used to compare the mean scores of each domain across selected demographic variables. The mean age of the disabled students was 21.7 years old (SD=1.9), while that of the non-disabled students was 22.3 years old (SD=2.6). As expected, the mean total QoL score (TotQoL) of the non-disabled students was higher than that of the students with disabilities. Except for the social relationships domain, the disabled students had significantly higher mean scores for the physical health, psychological health and environment domains compared with the control group. For the disabled group, no significant difference was observed between males and females in the mean TotQoL as well as in the four domains. Hearing-impaired students were found to score the lowest TotQoL among the categories of disabled students. They also scored the lowest for the social relationships domain, with a mean score of 5.91 compared with 16.26 and 15.98 for visually- and mobility-impaired students, respectively. In conclusion, WHOQOL-BREF is a useful instrument for assessing QoL for various groups of people. Accessing the QoL of youth including PWDs could assist relevant policy-makers and stakeholders in identifying problems faced by PWDs and in designing relevant intervention programmes.